Do anatomical contoured plates address scapula body, neck, and glenoid fractures and can these fractures be classified? – A multi-observer consensus study - De Wet, Johannes Jacobus (Division of General Surgery, 2022)
Background: The surgical management of scapula body, neck and glenoid fractures remains a challenge. This study focusses on templating an available anatomical pre-contoured plating system using 3D printed scapulae to assess the ability of these plates to address the aforementioned fractures and to determine consensus on classifying scapula body, neck and glenoid fractures. Methods: We used a cohort of twenty-two 3D printed fractured scapulae prototypes and an available anatomical pre-contoured plating system to determine anatomical congruency and fit. Nine investigators templated the scapula fractures using four pre-contoured plates and the investigators classified the twenty-two fractured scapulae using the Ideberg and AO/OTA classification system. Results: Eleven out of twenty-two fractures were found to be fixable using the plates under study. The long lateral plate addressed 83.3% of fractures involving the lateral border, while the glenoid plate was unable to adequately address any glenoid fractures. We observed good to excellent (p ≤ 0.001) inter-observer reliability for three of the four plates. The inter-observer reliability was moderate (ICC = 0.74) for the AO/OTA classification and good (ICC = 0.88) for the Ideberg classification. Conclusion: We believe that the anatomical pre-contoured plating system does not address all the fracture patterns encountered in clinical practice and further development in plate design is required. Good to moderate interobserver reliability were observed using the Ideberg fracture classification for intra-articular fractures and the AO/OTA classification for extraarticular fractures involving the body.